Revascularization of an acute right coronary artery long flap dissection with “Prolapsing knuckle wire technique” - Debasish Das; Satyapriya Mohanty; Abhinav Kumar; Anindya Banerjee; Pranjit Deb; Subash Pramanik (Heart India)
We present a rare case of revascularization of right coronary artery long flap dissection with novel prolapsing knuckle wire technique as the wire was repeatedly entering into the large medial dissection flap rendering the forward advancement of the wire impossible to cross the lesion. We negotiated the wire gently into the bottom of the dissection flap and pushed the wire gently so that the wire will ascend up and form a U loop inside the dissection flap. Further gentle advancement of the wire prolapsed the wire tip into the main lumen mimicking the fact that the dissection flap vomited out the wire into the main lumen. Keeping the tip of the wire in the main lumen, gentle pulling of the wire straightened the U loop, wire came out of the false lumen and gentle forward push with torque keeping the tip of the wire facing toward the lateral side the wire negotiated the microchannel present laterally and the lesion was crossed, predilated and successful coronary intervention was accomplished with Thrombolysis in Myocardial Infarction (TIMI) III flow. Our case is an interesting technique of guide wire negotiation in the presence of large dissection flap in acute coronary syndrome. Our case is also a rare illustration of a large spontaneous coronary dissection in an alcoholic.